2016
DOI: 10.1016/j.clim.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A plant-derived quadrivalent virus like particle influenza vaccine induces cross-reactive antibody and T cell response in healthy adults

Abstract: Recent issues regarding efficacy of influenza vaccines have re-emphasized the need of new approaches to face this major public health issue. In a phase 1-2 clinical trial, healthy adults received one intramuscular dose of a seasonal influenza plant-based quadrivalent virus-like particle (QVLP) vaccine or placebo. The hemagglutination inhibition (HI) titers met all the European licensure criteria for the type A influenza strains at the 3μg/strain dose and for all four strains at the higher dosages 21days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 71 publications
4
101
0
Order By: Relevance
“…For instance, we have recently shown that these VLPs rapidly access draining lymph nodes (29), where they associate with and activate immune cells, including B cells, macrophages, and dendritic cells (30). Furthermore, these vaccines elicit balanced humoral and cellular responses in both preclinical (young mice and ferrets) and clinical studies in healthy young adults (10)(11)(12)31). The current work confirmed the earlier observation of balanced humoral and cellular responses following plant-made VLP vaccination in the young mice and extended these findings to much older animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we have recently shown that these VLPs rapidly access draining lymph nodes (29), where they associate with and activate immune cells, including B cells, macrophages, and dendritic cells (30). Furthermore, these vaccines elicit balanced humoral and cellular responses in both preclinical (young mice and ferrets) and clinical studies in healthy young adults (10)(11)(12)31). The current work confirmed the earlier observation of balanced humoral and cellular responses following plant-made VLP vaccination in the young mice and extended these findings to much older animals.…”
Section: Discussionmentioning
confidence: 99%
“…and intranasal (i.n.) delivery (8)(9)(10)(11). These vaccines appear to elicit both strong antibody responses and long-lived and polyfunctional CD4 ϩ T cell responses (12).…”
mentioning
confidence: 99%
“…Their lead vaccine candidate, plant-derived influenza virus haemagglutinin (HA) virus-like particles, is currently being evaluated in phase 3 efficacy trials which, if successful, should lead to FDA approval by 2020. At the time of writing, influenza HA remains the only viral glycoprotein expressed in plants that has been evaluated in human trials (Pillet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Plants possess the eukaryotic post-translational protein modification machinery broadly similar to that of mammals, do not harbor human pathogens, and can be rapidly scaled up as economic biomass generator. The plant-produced recombinant HA is in clinical study [17].…”
Section: Vaccine Production Technologiesmentioning
confidence: 99%